Intersex related gene expression profiles in clams Scrobicularia plana: Molecular markers and environmental application. Issue 2 (30th June 2015) - Ciocan, Corina M.; Cubero-Leon, Elena; Langston, William J.; Pope, Nick; Cornelius, Keith; Hill, E.M.; Alvarez-Munoz, Diana; Indiveri, Paolo; Lerebours, Adelaide; Minier, Christophe; Rotchell, Jeanette M.
Highlights: Expression of intersex-related genes was analysed in clam gonads sampled from the Channel. Genes were differentially expressed at sites with varying levels of intersex and contaminants. Correlations between gene expressions, key contaminants and sampling sites were identified. No single gene expression studied correlated with intersex incidence. Abstract: Intersex, the appearance of female characteristics in male gonads, has been identified in several aquatic species. It is a widespread phenomenon in populations of the bivalve, Scrobicularia plana, from the southwest coast of the U.K. Genes previously identified as differentially expressed ( ferritin, testicular haploid expressed gene, THEG, proliferating cell nuclear antigen, PCNA ; receptor activated protein kinase C, RACK ; cytochrome B, CYB ; and cytochrome c oxidase 1, COX1 ) in intersex clams relative to normal male clams, were selected for characterisation and an environmental survey of the Channel region. Transcripts were significantly differentially expressed at sites with varying intersex incidence and contaminant burdens. Significant correlations between specific gene expressions, key contaminants and sampling locations have been identified, though no single gene was associated with intersex incidence. The results highlight the difficulty in understanding the intersex phenomenon in molluscs where there is still a lack of knowledge on the control of normal reproduction.